2013
DOI: 10.1038/bjc.2013.730
|View full text |Cite
|
Sign up to set email alerts
|

BOADICEA breast cancer risk prediction model: updates to cancer incidences, tumour pathology and web interface

Abstract: Background:The Breast and Ovarian Analysis of Disease Incidence and Carrier Estimation Algorithm (BOADICEA) is a risk prediction model that is used to compute probabilities of carrying mutations in the high-risk breast and ovarian cancer susceptibility genes BRCA1 and BRCA2, and to estimate the future risks of developing breast or ovarian cancer. In this paper, we describe updates to the BOADICEA model that extend its capabilities, make it easier to use in a clinical setting and yield more accurate predictions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
161
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 196 publications
(164 citation statements)
references
References 42 publications
0
161
0
3
Order By: Relevance
“…It can use the mutation screening result, molecular tumor characteristics like estrogen receptor (ER), progesterone receptor (PR), human epidermal growth factor receptor 2 (HER2), and basal cytokeratin (CK) expression (CK5/6 and CK14), and family histories of BRCA1/2 -associated cancers [59,60]. …”
Section: Breast Cancer Risk Prediction Modelsmentioning
confidence: 99%
“…It can use the mutation screening result, molecular tumor characteristics like estrogen receptor (ER), progesterone receptor (PR), human epidermal growth factor receptor 2 (HER2), and basal cytokeratin (CK) expression (CK5/6 and CK14), and family histories of BRCA1/2 -associated cancers [59,60]. …”
Section: Breast Cancer Risk Prediction Modelsmentioning
confidence: 99%
“…Information about the family history of cancer is an important predictor for estimating both the breast cancer risk and the probability of being a mutation carrier, for example, a carrier of a BRCA1 or BRCA2 mutation (1)(2)(3)(4)(5)(6). It has been suggested that a paternal origin of the BRCA mutation increases the breast cancer risk, whereas it decreases the ovarian cancer risk (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…The history of cancer(s) is then added, using the population-based Cancer Registry operated by the Icelandic Cancer Society (http://www.krabbameinsskra.is). By this method, comprehensive, electronically generated pedigrees (EGP) are made, enabling very accurate family history for risk assessment and calculations (Stefansdottir et al, 2013a, Lee et al 2014. However, like other methods of family history taking, this may also help to identify individuals who may be at increased risk of having a mutation in either the BRCA1 or BRCA2 gene, (hereafter referred to as BRCA mutations) or other inherited cancer predisposition.…”
Section: Introductionmentioning
confidence: 99%